2011
DOI: 10.1016/j.clinbiochem.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The stability of markers in dried-blood spots for recommended newborn screening disorders in the United States

Abstract: Minimizing both humidity and temperature in DBS transportation and storage environments is essential to maintaining sample integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 18 publications
(23 reference statements)
4
74
0
1
Order By: Relevance
“…9 Degradation of amino acids with high humidity is consistent with other studies reported that high humidity can influence dried blood spots. [14][15] Our results suggest that free carnitine (C0) was the least sensitive to 37 C and 45 C temperatures combined with humidity >70% over a period of eight days. The stability of free carnitine could be due the slight increase of its concentration by hydrolysis of esterified acylcarnitines.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…9 Degradation of amino acids with high humidity is consistent with other studies reported that high humidity can influence dried blood spots. [14][15] Our results suggest that free carnitine (C0) was the least sensitive to 37 C and 45 C temperatures combined with humidity >70% over a period of eight days. The stability of free carnitine could be due the slight increase of its concentration by hydrolysis of esterified acylcarnitines.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study has reported a 20-40% increase in free carnitine after one year of storage. [16][17] In addition, Adam et al 15 reported an increased C0 concentration during a 35-day study. However, the concentration of free carnitine could also be affected by hydrolysis of acylcarnitines during sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…31 In particular, DBS GALT activity decreases by > 60% when stored at low humidity and 37°C for 32 days, and by > 70% when stored at high humidity for 1 week. 32 As a result, this enzyme lability may contribute to false-positive screening results particularly in the summer. Because the Duarte (D2) allele also reduces enzyme stability, there may be a higher detection rate of DG galactosemia cases in the summer.…”
Section: Gale Deficiency (Type III Galactosemia)mentioning
confidence: 99%
“…We performed accelerated degradation studies of hemoglobins A and S according to the normalized study design we used to examine stabilities of 34 other disorder markers [4]. In accordance with that design, we stored eleven-member paired sets of the DBS materials at 37 °C in Bitran Series S zip-closure specimen bags containing humidity indicator cards that indicated by color change humidities below 30% (blue) and above 50% (pink).…”
Section: Accelerated Degradation Study Designmentioning
confidence: 99%
“…In 2011, we performed accelerated degradation studies of 34 disorder markers as part of routine evaluations of DBS materials prepared by the Newborn Screening Quality Assurance Program of the Centers for Disease Control and Prevention (CDC) to assist laboratories with monitoring the performance of their newborn screening tests [3].We examined the stabilities of those markers in a single normalized study design that included temperature and humidity variables [4].We were unable to include HbS (the marker for the three recommended sickle cell diseases) or HbA in our 2011 studies because of methodological limitations. A recently acquired high performance liquid chromatography (HPLC) system has enabled us to measure levels of hemoglobin species and examine their stabilities in DBSs stored under various environmental conditions.…”
Section: Introductionmentioning
confidence: 99%